Dietary cholesterol increases transcription of the human cholesteryl ester transfer protein gene in transgenic mice. Dependence on natural flanking sequences. - Jiang, X C (1992)
To investigate the regulation of expression of the human cholesteryl ester transfer protein (CETP) gene, transgenic mice were prepared using a CETP minigene linked to the natural flanking sequences of the human CETP gene. By using a transgene containing 3.2 kb of upstream and 2.0 kb of downstream flanking sequence, five different lines of transgenic mice were generated. The abundance of CETP mRNA in various tissues was determined on standard laboratory diet or high fat, high cholesterol diets. In three lines of transgenic mice the tissues expressing the human CETP mRNA were similar to those in humans (liver, spleen, small intestine, kidney, and adipose tissue); in two lines expression was more restricted. There was a marked (4-10-fold) induction of liver CETP mRNA in response to a high fat, high cholesterol diet. The increase in hepatic CETP mRNA was accompanied by a fivefold increase in transcription rate of the CETP transgene, and a 2.5-fold increase in plasma CETP mass and activity. In contrast, CETP transgenic mice, in which the CETP minigene was linked to a metallothionein promoter rather than to its own flanking sequences, showed no change in liver CETP mRNA in response to a high cholesterol diet. Thus (a) the CETP minigene or natural flanking sequences contain elements directing authentic tissue-specific expression; (b) a high cholesterol diet induces CETP transgene transcription, causing increased hepatic CETP mRNA and plasma CETP; (c) this cholesterol response requires DNA sequences contained in the natural flanking regions of the human CETP gene.